The Ongoing Crisis in Côte d’Ivoire: The Historic Responsibility of Félix Houphouët-Boigny - Jean-Claude MELEDJE (Ученые записки Института Африки Российской академии наук)
This article argues that the root causes of the conflict can be traced back to the leadership of Félix Houphouët-Boigny, the first President of the independent, post-colonial nation. Houphouët-Boigny failed to successfully manage a leadership transition from his generation to the next. During his three decades of rule, there were no plans made for his succession. When he ultimately died in office, the result was political, economic, and social instability. Consequently, the country was plunged into ongoing crises and conflicts. President Houphouët-Boigny had been the dominant political force of Côte d’Ivoire. His political skills made the country one of the most stable in the continent. Despite the rise of opposition from students, teachers, trade unionists and northern ethnic groups – all of whom were resentful of the southerner’s dominance of government, Houphouët-Boigny was able to restore calm through political dialogue. In 1987, Houphouët-Boigny’s advanced age – he was at least 81- contributed to the succession issue’s centrality in Ivorian politics. However, Houphouët-Boigny manipulated the Constitution. This caused frustration and set the stage for Houphouet-Boigny to remain in his role for the remainder of his life, despite a massive demonstration in Abidjan on May 31st, 1991, where 20,000 protesters chanted for ‘Houphouët-Boigny to resign.’ Consequently, a public leadership contest after Houphouët-Boigny’s passing reopened old wounds among interest groups which sought more economic and political power. This triggered the country’s ongoing crisis.